Meibomian Glands or Not? Identification of In Vivo and Ex Vivo Confocal Microscopy Features and Histological Correlates in the Eyelid Margin - Yu-jing Wang; Min Ke (Journal of Ophthalmology)
Purpose. In vivo confocal laser scanning microscopy (CLSM) is an emerging diagnostic tool allowing fast and easy microscopic tissue examination. For the diagnostics of pathological eyelid margin lesions, the knowledge of the normal eyelid margin is essential. Methods. We examined 18 eyelid margins of healthy humans using the in vivo CLSM device and 10 samples of healthy eyelid margins from donor sites with ex vivo CLSM and compared the findings to the corresponding histological sections of donor sites. Cross-section images of different depths and depths of different skin appendages were measured. Results. The depth observed by in vivo CLSM is less than 150 μm into the eyelid. Images of the epidermis and superficial dermis skin, appendages including hair follicle, and sebaceous catheters can be captured associated with histopathology and ex vivo confocal microscopy. In correlation with histopathology, we identified different layers of the eyelid margin, different layers of the epidermis, and skin appendages by ex vivo confocal microscopy. Conclusions. The study offers an overview of the in vivo confocal microscopy human eyelid margin characteristics in comparison to the standard histological examination and confirms that in vivo CLSM could not observe the meibomian gland acini structure.